Governance of Natural Resources in the Philippines : Lessons from the Past, Directions for the Future - World Bank (Washington, DC, 2013)
T his report analyzes natural resource management and governance in the Philippines, identifying recent trends, current challenges, and future goals. The first half of the report summarizes the status of the country's natural resources, describes sector policies, institutions, and budget mechanisms, and identifies impediments to improvements. The second half focuses on three crucial issues for natural resource governance: property rights, institutions, and financing. As part of its analysis of these three overarching issues, the report considers cross-cutting governance concepts such as participation, accountability, transparency, corruption, and service delivery. The report's final section offers conclusions and recommendations.